Witch Allegation in Nepal: A Case Study in Tamang Community of Kavrepalanchok District - Zoowa, Sabin Bahadur (Shiksha Shastra Saurabh, 2022)
Even in the 21st century, discrimination in Nepal due to witch allegations is seen as a social evil. The continued people’s movement has changed the political system but has not been able to change the attitude, faith, behavior, and social distortions of the Nepali people. As a result, people are involved in heinous and inhumane activities such as witch accusations. This study aims to explore this inhuman activity seen in the Tamang community which is one of the marginalized and disadvantaged groups in the Kavrepalanchok district in Nepal. The study of this phenomenon of witch accusations from the social point of view and perspective is another supportive objective of this study and to draw the attention of all key stakeholders to the significant scale, severity, complexity faced by Tamang women. Qualitative research with empirical & social perspectives based on both primary and secondary data has been used. Generally, the poor, miserable, helpless, ugly-faced, single women, widows, Dalits, Janajati, untouchables, etc. are mostly suspected of being witch allegations without any justice and proof in our context. Once, they are accused, it is difficult for the victims to stay in society for the rest of their life. However, recent laws have identified it as a social evil and strictly banned discrimination and accused the people on the ground of the witch allegations but in practice, the incident is still increasing. Thus, witches are the byproduct of the beliefs of witchcraft and the practices of witch allegations. This study helped to draw the attention of the policymakers, planners, local-level governments, and the elite group of the society to review policies and practices to overcome the society combating such inhuman activities.